Recent Development and Studies: The Consciousness’ Forming by Fractal Education and the Problem of Divinity - Marius, Arghirescu (New Ideas Concerning Science and Technology Vol. 12, 2021)
The paper analyzes the measure and the ways in which an individual or group consciousness can reach a ‘grace level’ (‚haric’ level) close to the maximum possible, considered of the Divinity. A first conclusion of the analysis is that the fractal, networked education, obtained from simple to complex and from an individual to a larger groups of (of group) consciences, within which the learning of an individual superior consciousness, in particular - teacher, professor, is transmitted to those spiritually guided by transmitting not only of his teaching but also of his attitude towards the transmitted teaching and the strategy of using it in society and the formation of individual and fractal consciences of haric level - understood as the highest value level of the psycho-social Good, requires a strategy of using the obtained orthodox-scientific teaching, based on completing the fundamental principles of the orthodoxy: purification, enlightenment, union with the Divinity, fight against evil, with the scientific principle of orthodox reciprocity. Another conclusion is that the possibility of the existence of a divine haric meta-consciousness, understood in the sense of haric spiritual leader of several haric super-consciences which are spiritual leaders of a significant number of superior consciences relative to the average level, exceeds the capacity of a single psycho-bio-social entity, resulting that a God with super-normal powers, capable of restoring the Good of the orthodox-scientific type in worldwide, can exist more as a judicial entity than as a single physical and spiritual entity, so- as a Divine Organization, more realistic and scientific being the concept of Godness, which must be both judicial and executive, based on scientific orthodoxy, which includes the principle of orthodox reciprocity. It results also that the possibility of spiritual leadership of the mankind by the Godness supposes energo-informational action with advanced technical means, such as telepathic amplifiers, which could also explain the transmission of the Holy Spirit and some reported paranormal manifestations such as the cases of "intelligent ghosts". It results also that the Godness may be recused by the scientific orthodoxism and the principles of the Providence must be modified in the form: orthodox-scientific cooperation with the Creation; orthodox-scientific leadership of the Creation and orthodox-scientific preservation of the Creation.